The role of workfare in striking a balance between incentives and insurance in the labour market - Torben M. Andersen; Michael Svarer (Center for Economic Studies and ifo Institute (CESifo), 2008)
Workfare policies are often introduced in labour market policies to improve the trade-off between incentives and insurance as an alternative to benefit reductions. Most of the debate on such policies has focussed on the direct effect of those participating in the scheme, and in particular the possible locking-in effect reducing job search. In a general equilibrium search framework, we show that the effects of workfare policies critically depend on the response of those not in the programme when they take into account that workfare is a condition for remaining eligible for unemployment benefits. This implies that unemployed not yet in workfare may search more for regular jobs, and employed may accept lower wages since the outside option becomes less attractive. Introduction of workfare policies into an unemployment insurance scheme is shown to contribute to a reduction in both open and total unemployment. It is also shown that the direct search effects of workfare policies are a poor indicator of the overall effect workfare policies have on labour market policies.
Keywords: J68; 330; active labour market policy; risk; search; unemployment; Workfare; Arbeitsmarktpolitik; Ökonomischer Anreiz; Flexicurity; Arbeitslosenversicherung; Arbeitsplatzsuchmodell; Theorie